Sosialisi Peraturan Daerah Kota Jayapura Nomor 33 Tahun 2023 Tentang Pajak Daerah dan Retribusi Daerah Kepada Juru Parkir di Distrik Jayapura Utara - Wospakrik, Decky (Yayasan Daarul Huda Kruengmane, 2025)
Regional Regulation Number 33 of 2023 of Jayapura City regulates Regional Taxes and Regional Levies, including parking levies. This regulation establishes general provisions regarding the subjects, objects, and rates for various types of regional taxes and levies in the City of Jayapura. On-street parking fees fall under the category of General Service Retribution. This service method was carried out through lectures and discussions held on Monday, April 21, 2025, in the city of Jayapura, specifically in front of Toko Gelael and around Jl. Halmahera, Jl. Percetakan, and Jl. Irian, North Jayapura district. The implementation of appropriate parking fees and the challenges in the field still use a manual system, where there are still issues such as parking users paying below the parking fee for certain reasons and parking attendants not providing parking tickets. The result of this service is the understanding of parking attendants that parking fees contribute to the local revenue (PAD) of Jayapura City. And how to prevent parking fee manipulation by using QRIS, which gradually transforms the manual system to a digital system with e-parking.